Compaixão, expiação e indiferença do Estado: notas sobre a tragédia de Entre-os-Rios - Pedro Araújo (Investigação, 2016)
On 4th March 2001, at around 9.10pm, the collapse of the fourth pillar of Hintze Ribeiro Bridge caused part of the bridge deck to give way. A bus with fifty-three people on board and three passenger vehicles with six occupants plunged into the turbulent waters of the River Douro. Fifty-nine people lost their lives.ALT_QUEBRA_LINHAStarting from the study of the partial collapse of Hintze Ribeiro Bridge, a sociology with disasters is proposed with three main objectives that are explored in this book. The first objective is to focus on how the political crisis ensuing from the event is managed. The second is to look at the interpellating power of death and suffering and, more precisely, at the process of their politicization. The third objective is to highlight the inscription of the event, classified as extraordinary, in a temporal continuous in which three segments of time are considered: the time before the disaster; the time during which the disaster occurs (the emergency period); and the period of quasi-silence about the disaster (the long term). The inscription of the event in a longer temporality is crucial for the fourth and central objective of this thesis: to identify the type of governance practice of a territory and a population affected by an extraordinary event and the distinct materialities it assumes during both the emergency phase and in the long term.